A swarm of small shield volcanoes on Syria Planum, Mars - Rita Baptista, Ana; Mangold, Nicolas; Ansan, Véronique; Baratoux, David; Lognonné, Philippe; I. Alves, Eduardo; A. Williams, David; E. Bleacher, Jacob; Masson, Philippe; Neukum, Gerhard (Journal of Geophysical Research, 2008)
International audience This study focuses on the volcanism in Syria Planum, located at the center of the Tharsis bulge at an altitude of 6 to 8 km above Mars datum. Syria Planum was previously recognized as a center for the tectonic activity of Tharsis, but not as a major locus for volcanic activity, despite its centrality over the bulge. Using high-resolution images from the high resolution stereo camera on Mars Express combined with Mars Observer Laser Altimeter data, we have characterized a volcanic system that reveals a number of very interesting aspects of Mars volcanism. We identified a swarm of tens of coalesced shallow volcanic edifices, typically 10–30 km diameter, 0.1–0.2 km high, and with slopes around 0.5°. These characteristics are similar to those of small shield volcanoes found in Iceland. In addition, an intermediate-sized volcano, which is the source of lava flows that extend over >200 km, is observed west of this shield swarm. Our study characterizes a previously unrecognized volcanic assemblage on Mars which appears to be much more developed than was documented before, in terms of morphology, inferred origin, and periodicity of eruption. The estimated lava flux of the Syria Planum volcanoes is of the same order as the lava flux of Tharsis Montes. These characteristics suggest that Syria Planum experienced a very specific style of volcanism, which we dated to the Hesperian period.